Effects of Sowing Dates, P Levels and Rhizobium Treatment on Seed Yield in French Bean cv. Contender in Hills - D.K. RANA; S.S. RAWAT; S.P. UNIYAL; A.C. MISHRA (Seed Research, 2026)
This investigation was conducted in French bean cv. ’Contender’ sown at dates viz., 15 June, 15 July, 15 August and 15 September applied with four phosphorus levels viz., no P application, 30 kg P/ha, 60 kg P/ha and 90 kg P/ha and seed with and without treatment with Rhizobium phaseoli culture. The treatment with 15 August sowing, 90 kg P2O5/ha and seed treatment with Rhizobium culture was found most effective for highest values of nodulation, plant height, number of pods per-plant, grains per pod and seed yield per hectare.